The Place And Importance Of Pilgrimage Tourism In The Tourism Industry (Eurasian Research Bulletin, 2023)
The article describes the description of pilgrimage tourism and its essence. Also, statistical analyzes and forecasts are presented about the importance of pilgrimage tourism in the tourism industry today. In the conclusion, the role and importance of pilgrimage tourism in the quality of tourism in Uzbekistan is discussed.